Variation in fibre volume and orientation in walls: experimental and numerical investigations. (December 2016) - Žirgulis, Giedrius; Švec, Oldřich; Geiker, Mette Rica; Cwirzen, Andrzej; Kanstad, Terje
Abstract: Previous research with fibre‐reinforced slab elements has shown that the surface roughness of formwork and the presence of rebars affect fibre orientation and fibre volume distribution. This paper discusses the orientation and volume distribution of steel fibres in wall elements cast from a single point. Aparticular focus of the work was the effect of formwork tie ba rs on fibre orientation and distribution. Numerical simulations and X‐ray computed tomography were appliedto quantify the fibre orientation and distribution, and the mechanical performance was determined using three‐point bending tests on sawn beams. The Thorenfeldt model (applied in the Norwegian proposal for the new fibre‐reinforced concrete guideline) was used to estimate the residual flexural tensile strength based on fibre orientation and distribution. The simulation results show that the fibre orientation can be related to the flow pattern. The results indicate a large variation in fibre orientation, which was confirmedexperimentally. The fibre volume distribution was mostly uniform, except for an area with fewer fibres at the casting point. The large variation in fibre orientation was reflected in a large variation in residual flexural tensile strengths. Weak zones due to anisotropic fibre orientation, caused by formwork tie bars, were observed.